A review on Tulasi (Ocimum sanctum Linn.) - Kavyashree, MR; Harini, A; Hegde, Prakash L; Pradeep, Dr. (Journal of Drug Delivery and Therapeutics, 2019)
Ocimum sanctum Linn is one of the important medicinal plant; known as holy basil. It is commonly available and cultivated across the India and it is having many therapeutic usages. And it is widely used in Ayurveda for the treatment of various disorders. It is extensively used as antioxidant, immune-modulatory, antipyretic, anticancer, chemo-preventive, radio-protective, anti-hypertensive and cardio protective and antimicrobial activity etc. The present article provides all necessary information regarding its classical literature and research updates on Phytoconstituents and pharmacological activities. Keywords:  Ayurveda, Tulasi, Ocimum sanctum Linn.